Job Loss and the Couple Experience of Coping - Schalk, Kyle J. (Canadian Journal of Counselling and Psychotherapy, 2016)
The couple experience of job loss and unemployment was explored using an existentialphenomenological approach. Through individual and couple interviews, married participants described psychological challenges, relationship barriers, and communication difficulties. Coping strategies—including practical interventions, relationship variables, and cultivating hope—were also explored. Participants described after-effects, including ongoing vulnerability as well as new appreciation and meaning. A discussion of the results, study limitations, and suggestions for counselling and further research is provided.